High cycle fatigue simulation: A new stepwise load-advancing strategy. (15th August 2015) - Barbu, L.G.; Oller, S.; Martinez, X.; Barbat, A.
Highlights: A brief description of a CDM fatigue model for high-cycle fatigue is made. An automatic load-advancing algorithm is proposed. The capabilities of the algorithm are shown in some simple numerical examples. Validation of the constitutive model and advancing strategy is made by comparison to experimental results. Abstract: A stepwise load-advancing strategy for cyclic loading will be presented in this paper that yields convergence in reasonable computational time for highly nonlinear behaviour occurring past the S – N curve. The algorithm is also effective when dealing with combinations of cyclical loads. The strategy is coupled to a continuum damage model for mechanical fatigue analysis. A brief overview of the constitutive model is also presented although it is not the main focus of this work. The capabilities of the proposed procedure are shown in two numerical examples. The model is validated by comparison to experimental results.